Workshop on Implementation of Technology in Learning - Rahadian, Dian; Nursiami, Eva Fauzi; Rosmiati, Rini (Indonesian Journal of Community Empowerment (IJCE), 2023)
Education in Indonesia, in particular, faces the challenge of transforming itself into a more innovative and interactive learning system. Implementing learning media that utilizes modern technology is a crucial step in improving the quality of education and student engagement in the learning process. The workshop was designed with an interactive approach to ensure the active involvement of all participants. Sessions included theoretical presentations on the importance of technology in education, the use of social media and digital platforms, and discussions on practical experiences using technology in teaching. Workshop discussions emphasized the importance of collaboration in implementing technology in education. Participants noted that technology adoption is not solely technical but also requires approval and support from educational management, as well as collaboration between educators and third parties. Therefore, the workshop included sessions where participants could work collaboratively to create technology-based learning content. This collaboration is crucial because cooperative learning models are introduced in educational contexts with the aim of strengthening teamwork and enhancing understanding of the concepts taught.